Overall Survival Analysis of a Phase II Randomized Controlled Trial of a Poxviral-Based PSA-Targeted Immunotherapy in Metastatic Castration-Resistant Prostate Cancer - Kantoff, Philip W. (American Society of Clinical Oncology, 2010)
PURPOSE: Therapeutic prostate-specific antigen (PSA) –targeted poxviral vaccines for prostate cancer have been well tolerated. PROSTVAC-VF treatment was evaluated for safety and for prolongation of progression-free survival (PFS) and overall survival (OS) in a randomized, controlled, and blinded phase II study. PATIENTS AND METHODS: In total, 125 patients were randomly assigned in a multicenter trial of vaccination series. Eligible patients had minimally symptomatic castration-resistant metastatic prostate cancer (mCRPC). PROSTVAC-VF comprises two recombinant viral vectors, each encoding transgenes for PSA, and three immune costimulatory molecules (B7.1, ICAM-1, and LFA-3). Vaccinia-based vector was used for priming followed by six planned fowlpox-based vector boosts. Patients were allocated (2:1) to PROSTVAC-VF plus granulocyte-macrophage colony-stimulating factor or to control empty vectors plus saline injections. RESULTS: Eighty-two patients received PROSTVAC-VF and 40 received control vectors. Patient characteristics were similar in both groups. The primary end point was PFS, which was similar in the two groups (P = .6). However, at 3 years post study, PROSTVAC-VF patients had a better OS with 25 (30%) of 82 alive versus 7 (17%) of 40 controls, longer median survival by 8.5 months (25.1 v 16.6 months for controls), an estimated hazard ratio of 0.56 (95% CI, 0.37 to 0.85), and stratified log-rank P = .0061. CONCLUSION: PROSTVAC-VF immunotherapy was well tolerated and associated with a 44% reduction in the death rate and an 8.5-month improvement in median OS in men with mCRPC. These provocative data provide preliminary evidence of clinically meaningful benefit but need to be confirmed in a larger phase III study.